Internalization of Student Discipline Character thru Worship Habituation: A Moral Shield Study against the Impact of Modernity in the Southern Route - Wismanto Wismanto; Abdul Hopid; Mhd. Lailan Arqam (Journal of Indonesian Progressive Education, 2026)
The phenomenon of the degradation of discipline character and lifestyle changes due to regional infrastructure development (Southern Cross Road) poses a serious challenge to self-control among elementary school students. This study aims to analyze the mechanism of habituating Duha prayer as an instrument for strengthening student discipline. Using a qualitative case study approach, data were collected thru participatory observation, in-depth interviews, and documentation. Analysis was conducted by integrating Thorndike's Law of Exercise theory and Thomas Lickona's character education concept. Research findings indicate that structured habituation thru pre-, process, and post-worship stages effectively builds three dimensions of discipline: time discipline, instructional discipline, and regulatory discipline (self-control). The success of this program is determined by the strategic partnership of religious leaders and the collective example set by teachers, although it is still hindered by factors such as teacher dissonance and the family environment. This study concludes that consistent worship habituation functions as a moral shield for students in facing the negative impacts of modernity and sociological changes in the region.